MUSIC PRODUCED BY A COMBINATION OF HINDUSTANI AND WESTERN MUSIC - WITH SPECIAL REFERENCE TO THE ELEMENTS (FUSION-MUSIC): हिन्दुस्तानी एवं पाश्चात्य संगीत पद्धति के सम्मिश्रण द्वारा उत्पन्न संगीत- तत् वाद्यों के विशेष संदर्भ में (फ़्यूज़न-म्यूज़िक) - Srivastava, Kinshuk; Kumari Vaishnav, Uma (International Journal of Research -GRANTHAALAYAH, 2015)
Classical music is a precious element of Indian culture. Any religion, civilization, culture, tradition is attained with music as well as perpetuity. Every living element on earth is associated with music and the living beings are connected by music only. Because human is emotional and people of different cultures are also connected through the expressions expressed through music. शास्त्रीय संगीत भारतीय संस्कृति का एक अनमोल तत्व है। कोई भी धर्म, सभ्यता, संस्कृति, परम्परा संगीत के साथ ही चिरन्तनता को प्राप्त होता है। पृथ्वी पर प्रत्येक जीवन्त तत्व संगीत से जुड़ा है और प्राणीमात्र आपस में संगीत द्वारा ही जुड़े है। क्योंकि मानव भाव-प्रधान है और संगीत के द्वारा अभिव्यक्त भावों के माध्यम से ही भिन्न संस्कृतियों के लोग भी आपस में जुड़े हैं।